Hara-Gauri Lintel - Temples of India Project Team (Jio Institute, 2024)
It is a trishakha (three vertical bands or branches) lintel having a nagashakha (serpent branch), inner patravalli (foliage pattern), and a mithunashakha (amorous couple branch) at the top, with the central figure of Shiva-Parvati in alingana (embrace), interspersed by kirtimukhas (face of glory). Two standing mithuna (amorous couple) figures are present at the end of the lintel.